The Effect of Barley and Lysine Supplementation of Pasture-Based Diet on Growth, Carcass Composition and Physical Quality Attributes of Meat from Farmed Fallow Deer (Dama dama) - Kudrnáčová, Eva; Bureš, Daniel; Bartoň, Luděk; Kotrba, Radim; Ceacero, Francisco; Hoffman, Louwrens C; Kouřimská, Lenka (Animals, 2019)
Fallow deer (Dama dama) are important meat producing species providing venison and other products to an international market. The present study investigated the effects of different feed rations on the growth, carcass characteristics and physical attributes of the longissimus lumborum (LL) and semitendinosus (SET) muscles of 45 farm-raised male fallow deer. The animals were divided into three separate groups: 15 pasture-fed (P), 15 pasture-fed and supplemented with barley (B), and 15 pasture-fed and supplemented with barley and lysine (BL). The animals were slaughtered at an average age of 17 months at three time points: after 155, 169 and 183 days on feed. The addition of barley to the feed ration significantly increased weight gain and had positive effects on slaughter and carcass weights, dressing-out proportion, carcass composition, the weight of LL muscle, and increased the redness, yellowness and chroma values of LL muscle. The supplementation with lysine reduced the amounts of carcass and internal fats without compromising other economically important traits.
Keywords: muscle; performance; diet; meat quality; venison